How the Circle Model can purpose-orient entrepreneurial universities and business schools to truly serve society. Issue 2 (6th March 2017) - Muff, Katrin
Abstract : Purpose: The purpose of this paper is to outline a path for entrepreneurial universities to embrace their purpose as custodians of society and to hardwire it institutionally. Design/methodology/approach: The paper is conceptual in its approach, drawing on practical and theoretical insights in the fields of responsible leadership, business sustainability and transformational change. The resulting Circle Model offers a developmental perspective connecting individual and organizational development in service of society. Findings: A key finding lies in expanding the current understanding of an entrepreneurial university beyond its organizational effectiveness to become a true custodian of society in the way it educate, researches and lives this intended purpose. The model offers a next conceptual step for the 50+20 vision (Muff et al., 2013) which had outlined a radical new role for business schools. Research limitations/implications: More research is required to understand how not only the educational and research strategies but also the organizational structure can be transformed to serve a given purpose. Practical implications: Concrete insights and examples of the developmental perspective of the model illustrate the opportunities for educating responsible leaders, for consulting business organizations to serve the common good, and for walking the talk by hardwiring a purpose-driven organization. Originality/value: The originality of the paper lies in the introduction of the idea of a common space of sustainability and responsibility as a foundation to reorient education and research of an entrepreneurial business school and hardwire its organizational structure truly around purpose.